Fibromyalgia Syndrome in Patients with Nasal Septum Deviation. Issue 2 (June 2013) - Ozsahin, Mustafa; Yaman, Hüseyin; Belada, Abdullah; Ataoglu, Safinaz
Abstract Objectives: Some studies conducted with patients with obstructive sleep apnea syndrome [OSAS] have suggested an association between sleep-disordered breathing [SDB] and fibromyalgia syndrome [FMS]. Nasal septum deviation [NSD] is a common physical disorder of the nose and it manifests itself with similar complaints, like respiratory distress and headache, as in patients with OSAS. The aim of this study was to determine the frequency of FMS in patients with NSD. Methods: Consecutive patients, 18 to 60 years old, evaluated in an academic otorhinolaryngology outpatient clinic were prospectively recruited for this study. Patients with nasal septal deviation were included in the nasal septum deviation group. Patients without nasal symptom deviation were recruited to serve as controls. All recruited cases were assessed by a single physiatrist for FMS. The FMS diagnosis was made on the basis of the 1990 American College of Rheumatology Research Classification Criteria. Results: One hundred ninety-nine consecutive patients, 18 to 60 years old, were enrolled in the study. Patients were divided into two groups as those with nasal symptom deviation [n = 115] and those without nasal symptom deviation [control group, n = 84]. Fibromyalgia syndrome was diagnosed in six NSD patients [5.2%] and in four [4.8%] control patients. No differences were noted in the prevalence of FMS between the two groups [p = 0.578]. Conclusion: In this study, we demonstrated a normal prevalence of FMS among patients with NSD. Although some studies suggest a relation between sleep disordered breathing and FMS, we could not find any relationship between NSD and FMS. This result may be associated with the fact that patients with OSAS and morbid obesity were excluded from our study. Future studies are warranted to clarify the association between obstructive sleep-disordered breathing and FMS.